FOTOGRAFI PANGGUNG SOLO INTERNATIONAL ETHNIC MUSIC DI KORAN SOLOPOS DAN KOMPAS TEKNIK DAN ESTETIS - Prasetyo, Andry (Capture : Jurnal Seni Media Rekam, 2010)
Stage Photography is one of the branches of science photography, which is devoted to the documentation of art stage. The documenting function is similar to the function of general photography. The branch of state photography more focuses on portraying the scenes on the stage. It becomes something special for both amateur and professional photographers because it requires a high sensitivity, concentration, skills, proficiency and special carefulness. Stage photography is absolutely necessary in the modern mass media, either as a standalone news as well as illustrations to support the news writing. Stage photography with the reality of the value, will help in the mass media to provide more complete information for the audience of readers. The stage photography of Solo International Music Performed which was published in the mass media Solopos and Kompas is the result of the recording of the photographer who has a sense of sensitivity, concentration, skill, finesse and accuracy. The papers published in the mass media can not be detached from the values and aesthetics rules, considering the photos will be witnessed by thousands of the human eye.Keywords: Stage Photography, Technique and Aesthetics.